Solution processed Group V1 transition metal dichalcogenides : a study on conductive hybrids and photoconductivity for future applications in printed electronics - Cunningham, Graeme (Trinity College (Dublin, Ireland). School of Physics, 2014)
Transition metal dichalcogenides (TMDs) constitute a class of inorganic layered compound with generalised MX2 stoichiometry, where M denotes a transition metal atom and X a chalcogen atom of sulfur, selenium or tellurium (S, Se or Te). As such over forty different varieties may be realised, covering the full array of electronic properties from insulators and semiconductors through to metals and superconductors, depending on the combination of M and X.[i] TMD monolayers are -0.7 nm thick and consist of a hexagonal plane of transition metal atoms sandwiched between two displaced hexagonal planes of chalcogen atoms as X-M-X. Like graphene, these materials exhibit interesting physical phenomena when manifested in the monolayer limit.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.